Antimicrobial Resistance Genes in Clinical Escherichia coli Strains from Livestock and Poultry in Shandong Province, China During 2015–2020 - Miaoli Wang; Shaopeng Wu; Yao Wang; Feng Chen; Zhangqi Shen; Zouran Lan (Antibiotics)
Antimicrobial resistant (AMR) Escherichia coli (E. coli) isolated from animals may lead to antibiotic treatment failure and economic losses to farmers. The co-existence of antimicrobial resistant genes (ARGs) in the same isolate presents a major challenge for the prevention and control of infection in multidrug-resistant (MDR) Gram-negative organisms. There have been a lot of studies on the antibiotic resistance of E. coli in livestock and poultry, but few of them have focused on clinical pathogens. Objective: The aim of this study was to explore the genetic characteristics, co-occurrence, and correlations between ARGs of E. coli isolated from the pathological tissues of livestock and poultry in Shandong Province, East China during 2015–2020. Methods: A total of 158 E. coli strains were collected and subjected to antimicrobial susceptibility testing and sequencing by whole-genome Next Generation Sequencing (NGS). Results: MDR strains accounted for 46.20% of the 158 E. coli strains with the highest resistant rate of ciprofloxacin (71.52%). In addition, strains with blaNDM-5/mcr-1.1 and mcr-1.1/mcr-3.24 were found in chickens, while three strains with Tet(X4) were found in pigs. In addition, the most common serotypes detected were the O serotype (76/158) and H serotype (36/158). Moreover, seventy-one STs were found and the most common STs were ST10 (6.33%), ST155 (6.33%), and ST101 (5.69%). The genetic environment analysis of the phylogroups revealed that E. coli belonging to phylogroup B1, phylogroup A, and phylogroup C constituted 39.87%, 27.85%, and 15.19%, respectively. Through the correlation analysis, mcr genes were observed to have certain relationships with ARGS such as blaTEM, floR, catA/B, and oqx. Conclusions: This study demonstrates the high prevalence and gene diversity of MDR E. coli isolated from a clinic in Shandong Province, East China. We predicted the transmission risk of animal-borne Tet(X4)-bearing and mcr-harboring E. coli to public health and provided insight into the relationship of co-existence or co-transfer between mcr with ARGS. These relationships present a great challenge for the infection control of MDR Gram-negative organisms.